High speed elevator dynamic analysis and control on severe conditions - Lenz, Wagner B.; Ribeiro, Mauricio A.; Goncalves, Giovanna; Balthazar, Jose M. [UNESP]; Rocha, Rodrigo Tumolin; Tusset, Angelo M. (My University, 2020)
The advent of verticalization after WWII made the densification on major cities. Thus the high-rise building was the solution to accommodate the vast amount of people on cities. The elevator was a solution to vertical transport of cargo and people. However, a safe, fast and stable travel it a basic requirement to ensure a good public perception. Even, on extreme cases of high building, high speeds on seismic region. The high speed elevator are subject to high impact and must stabilize the motion. In this paper a mathematical model of elevator with a cubic spring with a big impact is use to destabilize the motion. The dynamic of the elevator is determined to reduce the motion varying the angle of the rollers and the excitation frequency. The results shows a jump on the motion when the phase angle is different than 180°. In addition, the chaotic region can be controlled with a pneumatic actuator and reduce the general displacement.
Keywords: Control; High speed lift; Pneumatic actuator; SDRE